Synthesis and photoresponse study of vertically oriented CuO/ZnO nanorod arrays based on solution methods. (June 2022) - Du, Shiyu; Yu, Naisen; Zhao, Liang; Li, Haiou
Abstract: Low temperature solvothermal method is employed to fabricate hierarchical CuO coated ZnO Nanorod Arrays (NRs) on p-Si. The device is characterized and the photoluminescence result indicates that ZnO NRs coupling with CuO nanostructure has high optical quality. Meanwhile, the experiment shows that obtained detector displays excellent infrared (IR) light sensing properties with fast response without external bias. The device has excellent stability and repeatability under 940 nm at zero bias voltage. The dark current of CuO@ZnO NRs device is 7.1 × 10 −10 A, and Ilight /Idark ratio is 155. Furthermore, the response results indicated that the coupling of CuO with and ZnO NRs to construct heterojunction nanostructure has fast response speed and responsibility (<1.5 ms). The unique hierarchical CuO@ZnO NRs will offer high surface-to-volume ratio and efficient electron transport which can accelerate carrier separation and facilitate electron-hole transfer. It will provide an effective method to assemble high performance photodetectors based on metal oxide with low cost. Highlights: Low temperature solvothermal method is employed to fabricate hierarchical CuO coated ZnO Nanorod Arrays (NRs) on p-Si. CuO/ZnO Nanorod Arrays detector displays excellent infrared (IR) light sensing properties. The unique hierarchical CuO@ZnO NRs can accelerate carrier separation and facilitate electron-hole transfer.